Sales Territory Design and Salesforce Performance in the Detergent Manufacturing Companies: The Actual Kenyan Context - Mwangi, Benson Muchoki; Kibera, Francis N.; Kinoti, Mary; Obara, Magutu P. (European Scientific Journal, ESJ, 2021)
This paper focuses on determining the influence of sales territory design on salesforce performance in the detergent manufacturing companies in Kenya. Detergents play a critical role in our everyday lives by ensuring hygiene at our personal level, in our homes, in schools, institutions, and hospitals. Detergents have gained a lot of prominence since the onset of the Corona Virus (COVID-19) disease in 2019, as it has been proved that they play an important role in curtailing the transmission of the COVID-19 disease. The Salesforce plays an important role in organizations as they are the ones who in most cases interact with customers, provide information about their organization and products, provide prices, demonstrate how products are used, train customers, provide after sales service, and resolve any issues that may arise. The study was anchored on Expectancy Theory, Resource Based Theory, Equity Theory, and Agency Theory. The study adopted positivism philosophy and used a descriptive cross sectional design. The unit of analysis was the sales people in the detergent manufacturing companies in Kenya who are members of Kenya Association of Manufacturers as per list obtained from KAM in December 2018. The study used primary data which was collected by administering semi-structured questionnaires. The data was analyzed using a combination of both descriptive and inferential statics to describe the manifestations of the variables in the data collected, simple regression model was used to test the significance of the influence of sales territory design (independent variable) on the salesforce performance (dependent variable). Fischer distribution test (F-test) was used to test the significance of the independent variable and the overall model. The p-value for the F-statistic was used to determine the robustness of the model. This was done at 95% confidence level (p<0.05). The study found a strong relationship between sales territory design and salesforce performance. This depicts that sales territory design is critical in determining salesforce performance in detergent manufacturing companies in Kenya.